As a useful tool for inhibitors derived from lignocellulosic hydrolysates in ethanol production: Vitreoscilla hemoglobin (VHb) - Erman, A. G.; Sar, T.; Seker, G.; Akbas, M. Yesilcimen (Wiley-Blackwell, 2016)
[No abstract available]
41st FEBS Congress on Molecular and Systems Biology for a Better Life -- SEP 03-08, 2016 -- Kusadasi, TURKEY
Keywords: Gene